Long-term survival following upgrade compared with de novo cardiac resynchronization therapy implantation: a single-centre, high-volume experience. Issue 8 (25th May 2021) - Schwertner, Walter Richard; Behon, Anett; Merkel, Eperke Dóra; Tokodi, Márton; Kovács, Attila; Zima, Endre; Osztheimer, István; Molnár, Levente; Király, Ákos; Papp, Roland; Gellér, László; Kuthi, Luca; et al.
Abstract: Aims: Patients with a pacemaker or implantable cardioverter-defibrillator are often considered for cardiac resynchronization therapy (CRT). However, limited comprehensive data are available regarding their long-term outcomes. Methods and results: Our retrospective registry included 2524 patients [1977 (78%) de novo, 547 (22%) upgrade patients] with mild to severe symptoms, left ventricular ejection fraction ≤35%, and QRS ≥ 130ms. The primary outcome was the composite of all-cause mortality, heart transplantation (HTX), or left ventricular assist device (LVAD) implantation; secondary endpoints were death from any cause and post-procedural complications. In our cohort, upgrade patients were older [71 (65–77) vs. 67 (59–73) years; P  < 0.001], were less frequently females (20% vs. 27%; P  = 0.002) and had more comorbidities than de novo patients. During the median follow-up time of 3.7 years, 1091 (55%) de novo and 342 (63%) upgrade patients reached the primary endpoint. In univariable analysis, upgrade patients exhibited a higher risk of mortality/HTX/LVAD than the de novo group [hazard ratio (HR): 1.41; 95% confidence interval (CI): 1.23–1.61; P  < 0.001]. However, this difference disappeared after adjusting for covariates (adjusted HR: 1.12; 95% CI: 0.86–1.48; P  = 0.402), or propensity score matching (propensity score-matched HR: 1.10; 95% CI: 0.95–1.29; P  = 0.215). From device-related complications, lead dysfunction (3.1% vs. 1%; P  < 0.001) and pocket infections (3.7% vs. 1.8%; P  = 0.014) were more frequent in the upgrade group compared to de novo patients. Conclusion: In our retrospective analysis, upgrade patients had a higher risk of all-cause mortality than de novo patients, which might be attributable to their more significant comorbidity burden. The occurrence of lead dysfunction and pocket infections was more frequent in the upgrade group.